Robust Characteristics of the Laschamp and Mono Lake Geomagnetic Excursions: Results From Global Field Models - Korte, Monika; Brown, Maxwell C.; Panovska, Sanja; Wardinski, Ingo (Frontiers in Earth Science, 2019)
Data-based global palaeomagnetic field models provide a more complete view of geomagnetic excursions than individual records. They allow the temporal and spatial field evolution to be mapped globally, and facilitate investigation of dipole and non-dipole field components. We have developed a suite of spherical harmonic (SH) field models that span 50 to 30 ka and include the Laschamp (~41 ka) and Mono Lake (~33 ka) excursions. Palaeomagnetic field models depend heavily on the data used in their construction. Variations in palaeomagnetic sediment records from the same region are in some cases inconsistent. To test the influence of data selection and reliance on age models, we have built a series of SH models based upon different data sets. A number of excursion characteristics are robust in all models, despite some differences in energy distribution among SH coefficients. Quantities such as field morphology at the core-mantle boundary (CMB) or individual SH degree power variations should be interpreted with caution. All models suggest that the excursion process during the Laschamp is mainly governed by axial dipole decay and recovery, without a significant influence from the equatorial dipole or non-dipole fields. The axial dipole component reduces to almost zero, but does not reverse. This results in excursional field behaviour seen globally, but non-uniformly at Earth's surface. The Mono Lake excursion may be a series of excursions occurring between 36 and 30 ka rather than a single excursion. In contrast to the Laschamp, these excursions appear driven by smaller decreases in axial dipole field strength during a time when the axial dipole power at the CMB is similar to the power in the non-dipole field. We suggest three phases for the 50 to 30 ka period: (1) a broadly stable phase dominated by the axial dipole (50-43 ka); (2) the Laschamp excursion, with the underlying excursion process lasting ~5 ka (43-38 ka) and the surface field expression lasting ~2 ka (42-40 ka); (3) a weak phase during which axial dipole and non-dipole power at the CMB are comparable, leading to more than one excursion between 36 and 30 ka.